“You Shall Not Pass”—tight junctions of the blood brain barrier - Bauer, Hans-Christian; Krizbai, István A.; Bauer, Hannelore; Traweger, Andreas (Frontiers in Neuroscience, 2014)
Tissue barriers restricting the free diffusion of substances between the central nervous system and the systemic circulation are of great medical interest. Excessive leakage of blood-borne molecules into the parenchyma and the concomitant fluctuations in the microenvironment following a transient breakdown of the blood-brain barrier (BBB) during ischemic/hypoxic conditions or due to an autoimmune disease are detrimental to the physiology of nervous tissue.On the other hand, the treatment of neurological disorders is often hampered as only minimal amounts of therapeutic agents are able to penetrate a functional BBB or blood cerebrospinal fluid barrier. At the basis of the BBB are, next to an elaborate transporting machinery, intimate cell-cell contacts (tight junctions) creating not only a paracellular diffusion constraint but also enabling the vectorial transport across cell monolayers.More recent findings indicate that functional barriers are already established during development, protecting the fetal brain. As an understanding of the biogenesis of TJs might reveal the underlying mechanisms of barrier formation during ontogenic development numerous in vitro systems have been developed to study the assembly and disassembly of TJs. In addition, monitoring the stage-specific expression of TJ proteins during development has brought much insight into the “developmental tightening” of tissue barriers. Further, over the last two decades a detailed molecular map of tight junctions has emerged. TJs not only represent a cell-cell adhesion structure, but integrate various signaling pathways, thereby directly or indirectly impacting upon processes such as cell proliferation, cytoskeletal rearrangement, and transcriptional control.This review will provide a brief overview on the establishment of the BBB during embryonic development in mammals and a detailed description of the ultrastructure, biogenesis, and molecular composition of epithelial and endothelial TJs will be given.